Pendayagunaan Dana Zakat Melalui Pemberdayaan Ekonomi Masyarakat Di Baznas Kota Jambi - Agustina Mutia; Muhammad Subhan; Rizkia Safitri (Jurnal Publikasi Manajemen Informatika, 2023)
This study aims to determine whether the government of the National Amil Zakat Agency (BAZNAS) has implemented empowerment to the community. This research method uses a qualitative method which is sourced from the National Amil Zakat Agency (BAZNAS) office in Jambi City. The results in the research conducted, conclusions are obtained.(1). The planning stage of the Allocation of Zakat Funds at the National Amil Zakat Agency (BA-ZNAS) has been carried out in accordance with what has been done by BAZNAS in an effort to improve the standard of living of the community, especially in Jambi City. However, the lack of community efforts in an effort to increase the level of the economy, which initially became mustahik to increase the level to become muzakki, the community was reluctant to do so.(2) The application of the Allocation of Zakat Funds for community empowerment is appropriate in the view of Islamic economics which aims to increase income, and help free from hunger, and seeks to help.(3) The use of zakat funds at the National Amil Zakat Agency (BAZNAS) can be seen from the success of the community in increasing income with the assistance of zakat funds.